New Challenges in Residual Stress Measurements and Evaluation - Casavola, Caterina; Barile, Claudia; Moramarco, Vincenzo; Pappalettera, Giovanni (IntechOpen, 2020)
Residual stresses (RS) are stresses present inside materials even in the absence of any applied load. They are of capital importance because they can impact greatly on the mechanical strength of the material, on its dimensional correspondence to design specifications as well as on the fatigue life of the part. RS measurement and evaluation is currently an important research topic where a lot of challenges still need to be addressed. This book aims to provide the reader with an overview of the principal novelties in this field including current limitations and potential future developments. Both radically new experimental approaches as well as recent evolutions of consolidated ones will be presented, along with the latest novelties in the area of numerical residual stress evaluation.